1992
DOI: 10.1038/hdy.1992.167
|View full text |Cite
|
Sign up to set email alerts
|

Non-random mating in Adalia bipunctata (the two-spot ladybird). III. New evidence of genetic preference

Abstract: Isofemale lines of ladybirds produced from a selected stock varied widely in female preference for melanic males. An attempt to repeat these results failed. The ladybirds used in the repeat experiment were collected from a wild population in which melanic frequencies had dropped from 35 to 10 per cent in 3 years. In this repeat experiment, the overall mating rate was twice that of the original experiment. The failure of the repeat experiment can be attributed either to a loss of preference or to the preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…Kearns et al (1992) did not, however, confinn that female ladybirds could possess a simple mating preference for melanic males. O'Donald and Majerus (1992) subsequently presented further evidence that was consistent with a female preference for melanic males. This paper reports the results of further investigations into nonrandom mating in Adalia bipunctara.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Kearns et al (1992) did not, however, confinn that female ladybirds could possess a simple mating preference for melanic males. O'Donald and Majerus (1992) subsequently presented further evidence that was consistent with a female preference for melanic males. This paper reports the results of further investigations into nonrandom mating in Adalia bipunctara.…”
Section: Introductionmentioning
confidence: 83%
“…Previous papers (Kearns et al, 1990(Kearns et al, , 1992O'Donald and Majerus, 1992) have analyzed the evidence for nonrandom mating in the two-spot ladybird, Adalia bipunctata, and presented new data on the same subject. Kearns et al (1990Kearns et al ( , 1992 concluded that there was evidence that the melanic morph gained a general mating advantage over the 1Department of Genetics, Downing Street, Cambridge CB2 3EH, U,K.…”
Section: Introductionmentioning
confidence: 95%
“…Several genetically distinct color morphs exist in native Asian populations but in Kentucky, H. axyridis populations consist entirely of the succinea color morph, which is homozygous recessive for predominantly red-orange, rather than black, elytral color (Komai 1956). Previous studies that examined`color' in ladybird beetles have typically focused on distribution of spot patterns (Komai 1956;Holloway et al 1995) or comparisons between discrete color morphs (e.g., melanic vs. nonmelanic elytra; Tan and Li 1934;Kearns et al 1990Kearns et al ,1992O'Donald and Majerus 1992;Osawa and Nishida 1992). Elytral color is highly and continuously variable within the succinea morph, ranging from a deep crimson to a pale yellow-orange.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, a second set of isofemale lines subsequently derived from the same (Keele) population, exhibited no female preference, and the original isofemale lines now appeared to mate at random (Kearns et al 1992). O'Donald & Majerus (1992) suggested that the different behaviour resulted from a reduction in the frequency of the preference gene in the Keele population. A drop in frequency of melanic males from 0-35 to 010 was observed in the three years between the two studies, and it is possible the female mating preference may also have declined in frequency.…”
Section: Introductionmentioning
confidence: 96%